Biotic and abiotic factors affecting the microbiota of Chrysomelidae inhabiting wetland vegetation - Giulia Magoga; Matteo Brunetti; Lukasz Kajtoch; Alberto Spada; Matteo Montagna (Hydrobiologia, 2023)
A subject of particular interest concerns the understanding of which biotic and/or abiotic factors shape the insect’s microbiota composition and diversity. In this study, we focus our attention on the microbiota associated with leaf beetles (Coleoptera: Chrysomelidae) inhabiting a freshwater wetland in Northern Italy for investigating which factors shape it in this peculiar environment. A DNA metabarcoding approach targeting the 16S rRNA has been used to characterize the bacteria associated with seven leaf beetles species living in different zones of the wetland (trees/shrubs, meadow and emergent vegetation zones). The obtained results suggest that three factors potentially affecting microbiota diversity and composition are species membership in the first place, then living zone in the wetland and sex. Within the studied species, males were found possibly more prone to acquire bacteria from the surrounding environment, while females’ microbiota of most of the species resulted dominated by symbiotic bacteria (reproductive manipulators, e.g. Wolbachia , or other symbionts with functional roles in the species, e.g. Candidatus Macropleicola in Donacia genus). The present study, even if based on a limited sample size, contributed to exploring the factors affecting the composition and diversity of bacteria associated with Chrysomelidae.